Opening Ceremony of Fundamental IT Engineers Course - Anuwar Ali (OUM, 2006)
Speech of the President/Vice-Chancellor OUM, Prof Tan Sri Anuwar Ali on IT Engineers Course (MYFE 2006) at Open University Malaysia’ Kuala Lumpur Learning Center. Monday 9 January 2006